Aminomethylpyrene-based imino-phenols as primary fluorescence switch-on sensors for Al3+ in solution and in Vero cells and their complexes as secondary recognition ensembles toward pyrophosphate. Issue 99 (23rd September 2015) - Mahapatra, Ajit Kumar; Ali, Syed Samim; Maiti, Kalipada; Manna, Saikat Kumar; Maji, Rajkishor; Mondal, Sanchita; Uddin, Md. Raihan; Mandal, Sukhendu; Sahoo, Prithidipa
Abstract : Three aminomethylpyrene-based salicyl-imines, viz. L1, L2 andL3 were designed and synthesized for Al 3+ ion sensing. Abstract : Three aminomethylpyrene-based salicyl-imines, viz. L1, L2 andL3 were synthesized and characterized and their recognition of biologically relevant M n + ions was studied. These three receptors were shown to be selective and sensitive for Al 3+ among the 13 metal ions studied in a HEPES buffer medium by fluorescence, absorption, and visual emission color change with detection limits of 3.60, 2.13 and 2.16 μM, respectively, byL1, L2 andL3 . The interaction of Al 3+ with the three receptors (L1, L2 andL3 ) has been further supported by absorption studies, and the stoichiometry of the complex formed (1 : 1) has been established on the basis of emission and ESI-MS. Competitive ion titrations carried out reveal that the Al 3+ can be detected even in the presence of other metal ions of bio importance. The structure of the aluminium complexes and their mode of interactions were established by DFT calculations. TDDFT calculations were performed in order to demonstrate the electronic properties of receptors. Microstructural features ofL2 and its Al 3+ complex have been measured by AFM. Moreover, the utility of the receptorsL1, L2 andL3 in showing aluminium recognition in live cells has also been demonstrated using Vero cells as monitored by fluorescence imaging. In situ prepared [AlL1 ] and [AlL3 ] complexes were found to be sensitive and selective toward phosphate-bearing ions and molecules and in particular to pyrophosphate (PPi) among the other 15 anions studied; however, [AlL2 ] was not sensitive toward any of the anions studied.